Participatory Budgeting - Shah, Anwar (Washington, DC : World Bank, 2012)
This book provides an overview of the principles underlying participatory budgeting. It analyzes the merits and demerits of participatory budgeting practices around the world with a view to guiding policy makers and practitioners on improving such practices in the interest of inclusive governance. This publication includes five regional surveys, and seven country case studies can be found on the accompanying CD ROM. The study explains that participatory budgeting has been advanced by budget practitioners and academics as an important tool for inclusive and accountable governance and has been implemented in various forms in many developing countries around the globe. It adds that through participatory budgeting, citizens have the opportunity to gain firsthand knowledge of government operations, influence government policies, and hold government to account. However, participatory processes also run the risk of capture by interest groups. Captured processes may continue to promote elitism in government decision making. This book examines the potential and perils of participatory budgeting, as observed from practices around the globe. It is divided into three parts. Part I presents the nuts and bolts of participatory budgeting. Part II surveys experiences with participatory budgeting in various regions of the world. Part III (Vol. 2) is on the CD ROM accompanying this book, and it examines case studies of practices in seven countries.